2012
DOI: 10.1007/s00167-012-2251-8
|View full text |Cite
|
Sign up to set email alerts
|

Is osteoarthritis an inevitable consequence of anterior cruciate ligament reconstruction? A meta-analysis

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
189
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(212 citation statements)
references
References 50 publications
(82 reference statements)
14
189
4
5
Order By: Relevance
“…Individuals with ACL injury are at high risk of poor longterm outcomes (eg, osteoarthritis, [18][19][20] knee pain, 21 diminished quality of life [21][22][23] ), and early symptoms predict more severe knee pain and symptoms 6 years after an ACL injury. 24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction.…”
mentioning
confidence: 99%
“…Individuals with ACL injury are at high risk of poor longterm outcomes (eg, osteoarthritis, [18][19][20] knee pain, 21 diminished quality of life [21][22][23] ), and early symptoms predict more severe knee pain and symptoms 6 years after an ACL injury. 24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction.…”
mentioning
confidence: 99%
“…Physical therapists often see clients who ''feel'' ready for return to sport within 5 months after reconstruction and whose outcome measure scores also indicate readiness, yet these underlying processes are not optimized, and return to sport may therefore lead to further joint damage. 19 In Cupido and colleagues' study, while ROM and pain measures provided evidence of recovery, LEFS scores had not recovered after 26 weeks. In addition, joint biomechanics and biochemical markers of tissue degradation may not normalize until after 26 weeks post injury; 6,8 this has implications for current pathomechanical frameworks proposed for the aetiology of knee osteoarthritis (OA), a significant concern for anyone who has sustained an ACL ligament rupture.…”
mentioning
confidence: 90%
“…Similarly, a large study of 1434 individuals found a relationship between an increased period of time from injury to surgery and higher rates of concomitant joint injury when presenting for ACLR, including injury to meniscus and joint surfaces (Ralles, Agel, Obermeier, & Tompkins, 2015). People with concomitant injury to other knee structures at the time of ACLR report higher rates of osteoarthritis 10 to 20 years later (Claes et al, 2013;Keays, 2010;Magnussen et al, 2009;Murray et al, 2012;Øiestad et al, 2009;van Meer et al, 2015) and poorer patient-reported outcomes after ACLR including more knee pain, symptoms, poorer function and reduced QOL (Barenius et al, 2010;Cox et al, 2014;Dunn et al, 2015;Gerhard et al, 2012;Neuman et al, 2008;Røtterud et al, 2012;Røtterud et al, 2013).…”
Section: Time From Injury To Surgerymentioning
confidence: 99%
“…Concomitant cartilage and meniscus injury with or without surgical repair has also been associated with higher rates of early-onset knee osteoarthritis compared with an isolated ACL rupture (Claes, Hermie, Verdonk, Bellemans, & Verdonk, 2013;Keays, 2010;Magnussen, Mansour, Carey, & Spindler, 2009;Murray et al, 2012;Øiestad et al, 2009;van Meer et al, 2015). Additionally, worse outcomes (reduced physical activity level and knee function, more pain and symptoms)…”
Section: Concomitant Joint Injurymentioning
confidence: 99%
See 1 more Smart Citation